PENGARUH CARA BELAJAR, MOTIVASI BELAJAR,DAN PEMANFAATAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR - Effy Irmawati; Yon Rizal; Nurdin Nurdin (FKIP Unila, 2013)
This research aims to know the effect of a study manner, learning motivation and the use of facility to learn at school towards learning outcomes of students the social studies class VIII SMP Kartikatama Metro lessons years 2012/ 2013. Methods used in this research is a method of descriptive verifikatif by approach ex post facto capital. Population in this study consisted of 160 students. Sample in this study consisted of 115 people. Based on data analysis obtained result: ( 1 ) there is an influence of the students study manner toward learning outcomes of the social studies ( 2 ) there is an influence on motivation learn students against the social studies (3) there is an influence on the use of facility at school toward learning outcomes of the social studies ( 4 ) there is an influence of a studied manner, learning motivation, and the use of facility to learn towards learning outcomes of the social studies.Penelitian ini bertujuan untuk mengetahui pengaruh cara belajar, motivasi belajar dan pemanfaatan fasilitas belajar di sekolah terhadap hasil belajar IPS Terpadu siswa kelas VIII SMP Kartikatama Metro Tahun Pelajaran 2012/2013. Metode yang digunakan dalam penelitian ini adalah metode deskriptif verifikatif dengan pendekatan ex post facto. Populasi dalam penelitian ini berjumlah 160 siswa. Sampel dalam penelitian ini berjumlah 115 orang. Berdasarkan analisis data diperoleh hasil: (1) terdapat pengaruh cara belajar siswa terhadap hasil belajar IPS Terpadu (2) terdapat pengaruh motivasi belajar siswa terhadap hasil belajar IPS Terpadu (3) terdapat pengaruh pemanfaatan fasilitas belajar di sekolah terhadap hasil belajar IPS Terpadu (4) terdapat pengaruh cara belajar, motivasi belajar,dan pemanfaatan fasilitas belajar terhadap hasil belajar IPS Terpadu.Kata kunci: cara belajar, hasil belajar, motivasi belajar.